Travel Behaviour Impact on Muslim Identity and Halal Consumerism among Malaysian Young Travellers - Mohamed Ismail, Risyawati; James Noh (Halalsphere, 2022)
Muslim travellers continue to impact the tourism and hospitality industry significantly. This study attempted to study 121 Muslim travellers’ consumption behaviour and how it affected their travel behaviour. The research used a quantitative approach via structured questionnaires. The study’s motivation was to understand Muslim travellers’ travel behaviour better to offer adequate support, particularly when heading to non-Muslim countries. Issues regarding the inability to find payer’s rooms and Halal food have always presented challenges to these travellers while they are on the road. Findings indicated that Muslim identity positively impacted Halal travel behaviour and Halal consumerism. Despite being far from home and in a new environment, Muslims will ensure to consume Halal products and services on the road. In conclusion, this study indicated that travelling Muslims would look for products and services that comply with Syari’ah and enable them to practise their Islamic faith while on the road. This outcome solidified the importance of Islamic tourism and hospitality, apart from catering to the Halal food supply in various nations, including non-Muslim countries, which also received throngs of Muslim travellers all year.